BEDA CARANYO, SAMO ENAKNYO : MEDIA PROMOSI TALAMAK BOWL - Ramadhanty, Windy; Swasty, Wirania (Institut Bisnis dan Teknologi Indonesia, 2020)
Indonesia has a great and priceless culinary potential of the archipelago. The culinary industry sector in Indonesia currently has a vast and increasing market, because this culinary sector is quite promising because it has economic value but still has advantages. Talamak Bowl is a small and medium enterprise (SME) in Bandung that is engaged in culinary specialties of West Sumatra. This business is still not well known by the public and there has been no increase in sales. Seeing the increasing number of culinary industry SMEs in the city of Bandung, it is necessary to have strong and effective promotional activities in offering products to many audiences in order to be superior than the others. Overcoming the problems above, then the design of promotional media is carried out by using data collection methods through observation, interviews, questionnaires and literature and the analytical method used is a comparison matrix to form the design concept. After getting conclusions from the method, the promotional media that created are applied to the name card, ambient media, brochures, e-posters and other supporting media. This design was made by combining two concept which is illustration and product photography. This design is expected that the problems faced will be resolved